Socialization of Land Utilization for Communities for Sustainable River Waters Area Ecosystems in Nagari Sungai Sariak, Sungai Sariak Vii Koto District, Padang Pariaman Regency - Nefilinda; Rozana Eka Putri; Rika Despica; Meli Agusti; Yulius Rahmanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this community service is to socialize land use for the community for a sustainable watershed ecosystem in Nagari Sungai Sariak, Sungai Sariak VII Koto District, Padang Pariaman Regency. This service is carried out in order to increase public understanding regarding: 1). land use, 2). Maintenance of watershed ecosystems. The results of the service that has been carried out are: 1). Increased public understanding regarding wiser land use, 2). Increased public understanding regarding the importance of sustainable watershed ecosystems. So that the availability of river water for people's lives continues to exist and can support the livelihoods of the people in Nagari Sungai Sariak, Sungai Sariak VII Koto District, Padang Pariaman Regency.